Influencia de los factores biológicos, sociales y culturales en la adherencia a la vacuna contra el papiloma virus: una revisión sistemática - Ruilova Córdova, Dora Thalía (2025)
Human papillomavirus (HPV) is the most prevalent sexually transmitted infection worldwide, and vaccination has proven effective in cancer prevention. The objective of the review was to analyze the biological, social, and cultural factors influencing adherence to the HPV vaccine, examining their variability across different geographic and demographic contexts, as well as the strategies implemented to improve adherence. The methodology employed a systematic review based on the PRISMA model, incorporating publications from the last five years and selecting relevant sources from databases such as PubMed, Scopus, ProQuest, SCIELO, and LILACS. Quality assessment tools, including the JBI method, were used to estimate the risk of bias in the analyzed studies. The results highlighted that biological factors such as age and gender, along with social factors like educational level and access to healthcare services, are key determinants of adherence. Meanwhile, cultural and religious beliefs can act as either barriers or facilitators depending on the context. Variability in vaccination rates was also observed based on geographic location and socioeconomic status, with higher rates in urban areas where educational campaigns are more accessible. The most effective strategies identified include early-age vaccination, simplified access through flexible schedules and convenient locations, and educational campaigns aimed at dispelling myths about the vaccine. The discussion underscores the importance of designing culturally sensitive interventions tailored to the needs of each population. The conclusion emphasizes the urgency of inclusive public policies that integrate education, accessibility, and community participation to increase vaccination coverage and reduce disparities